modern arabic language, - mohamed ourniki (Journal of Science and Knowledge Horizons, 2022)
The text, especially the literary one, is a linguistic structure based on the rules and system of the language, which gives linguistic analysis its importance in revealing the meaning, and makes the language a common denominator in the analysis among all texts written in that language, taking into account the specificity of each text according to its subject, rhetorical level and speaker. It is not possible to deviate from this language in which the Qur’an was revealed to another if the book in which it was revealed is intended to be explained, because knowledge of the meanings of its words can only be taken from it. Ibn Faris said that knowledge in the language of the Arabs is obligatory for every responsible person related to knowledge of the Qur’an, Sunnah and fatwas because none of them can sing about it, and that is because the Qur’an was revealed in the language of the Arabs and the Messenger of God, peace and blessings be upon him, is Arabic, so whoever wants to know what is in the Book of God Almighty and what is in the Sunnah The Messenger of God, may God’s prayers and peace be upon him, from every strange word or wondrous system he did not find from the knowledge of the language appeared. That is why scholars stressed the denouncement of those who interpreted the Qur’an while ignorant of the Arabic language. He narrated on the authority of Mujahid, a student of Ibn Abbas, may God be pleased with them, saying: “It is not permissible for anyone who believes in God.” And on the last day, he is to speak in the Book of God if he is not knowledgeable in the languages ​​of the Arabs. Imam Malik was reported to have said: “I will not be given a man who interprets the words of God while he is not familiar with the Arabic language, but I will make him a violator.